The euro: A story of misunderstanding - Heiner Flassbeck; Friederike Spiecker (Intereconomics, 2011)
From the very beginning of the European Monetary Union the crucial institutions, the European Commission and the European Central Bank, led by mainstream economic thinking, were not up to their task of controlling the core of the system effectively. A huge gap in competitiveness among the member states has arisen due to German wage-dumping policy on the one hand and, on the other, wage growth in Southern Europe which is above the growth of productivity plus the inflation target of 2%. A European-wide coordination of wage policy is the only promising way to close this gap. However, as wages and competitiveness are not high on the agenda of the politicians responsible and their advisers, time to save the euro is running out.
Keywords: 330